β-Cyclodextrin-Based Nanosponges Functionalized with Drugs and Gold Nanoparticles - Isabel Asela; Orlando Donoso-González; Nicolás Yutronic; Rodrigo Sierpe (MDPI AG, 2021)
Drugs are widely used as therapeutic agents; however, they may present some limitations. To overcome some of the therapeutic disadvantages of drugs, the use of β-cyclodextrin-based nanosponges (βCDNS) constitutes a promising strategy. βCDNS are matrices that contain multiple hydrophobic cavities, increasing the loading capacity, association, and stability of the included drugs. On the other hand, gold nanoparticles (AuNPs) are also used as therapeutic and diagnostic agents due to their unique properties and high chemical reactivity. In this work, we developed a new nanomaterial based on βCDNS and two therapeutic agents, drugs and AuNPs. First, the drugs phenylethylamine (PhEA) and 2-amino-4-(4-chlorophenyl)-thiazole (AT) were loaded on βCDNS. Later, the βCDNS-drug supramolecular complexes were functionalized with AuNPs, forming the βCDNS-PhEA-AuNP and βCDNS-AT-AuNP systems. The success of the formation of βCDNS and the loading of PhEA, AT, and AuNPs was demonstrated using different characterization techniques. The loading capacities of PhEA and AT in βCDNS were 90% and 150%, respectively, which is eight times higher than that with native βCD. The functional groups SH and NH2 of the drugs remained exposed and allowed the stabilization of the AuNPs, 85% of which were immobilized. These unique systems can be versatile materials with an efficient loading capacity for potential applications in the transport of therapeutic agents.